PENGARUH PROGRAM KELUARGA HARAPAN DAN GAYA HIDUP TERHADAP KESEJAHTERAAN MASYARAKAT PENERIMA PROGRAM KELUARGA HARAPAN DI KOTA PALOPO - husni nurhasana (Dinamis : Journal of Islamic Management and Bussiness, 2023)
This thesis discusses the Influence of the Family Hope Program (PKH) and Lifestyle on the Welfare of Communities Recipients of the Family Hope Program (PKH) in Palopo City. This research aims to determine the influence of the Family Hope Program (PKH) on the welfare of PKH recipient communities in Palopo City in part, to determine the influence of Lifestyle on the welfare of PKH recipient communities in Palopo City in part, and to determine the effect of the Family Hope Program (PKH) and Lifestyle on the welfare of PKH recipient communities in Palopo City simultaneously. This type of research is quantitative to examine the influence of the Family Hope Program (PKH) and lifestyle on the welfare of the people who receive the Family Hope Program (PKH) in Palopo City. The population in this study were recipients of the Family Hope Program (PKH) in Palopo City. Sampling in this study used a simple random sampling technique and determined the number of samples using the Slovin formula. Based on this formula, the number of samples used was 99 people. Data was obtained through observation and questionnaires. Furthermore, this research data was processed using multiple linear regression analysis, t test, F test and coefficient of determination test. The results of this research show that the Family Hope Program (PKH) variable (X1) has a positive and significant effect on Community Welfare with a tcount value of 10.187 > ttable value 1.984 (Y) Lifestyle (X2) has a positive and significant effect on Community Welfare with a tcount value of 6.118 > ttable value 1.984 (Y) recipients of the family hope program in Palopo City. The Family Hope Program (X1) Lifestyle (X2) simultaneously has a significant effect on community welfare with an Fcount value of 107, 594 > Ftable value 3,090 (Y) for recipients of the Family Hope Program in Palopo City. The ability of the Family Hope Program (PKH) (X1) and Lifestyle (X2) in explaining the influence on community welfare (Y) of recipients of the Family Hope Program (PKH) in Palopo City is 68.5% and the remaining 31.5% is explained by other variables not included in the research. Keywords: Lifestyle, Family Hope Program, Community Welfare